Telomere length assessment in blood leukocytes of sarcoidosis patients ‎ - Abedini, Atefeh; Nadji, Seyed Alireza ‎; Sadr, Makan; Kiani, Arda; Alizadeh, Niloufar; Afshar, Hale (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background: In many chronic diseases such as IPF and COPD, accelerated aging and telomere shortening have been studied. Different studies have shown that these individuals have shorter telomere lengths than controls; this can be a marker of the progression and outcome of the disease. So far, a few studies have been evaluated the telomere length in sarcoidosis. In this study we try to determine the telomere length in sarcoidosis patients and compare with control subjects. Objective: Our aim is to compare telomere length in sarcoidosis patients and normal population. Methods: We select 58 sarcoidosis patients who were visited in the outpatient clinic of sarcoidosis in Masih Daneshvari Hospital.58 healthy control subjects were selected and tried to be sex-matched and age-matched with±2 years of age. Telomere length was measured by quantitative real time PCR as described by Cawthon on peripheral blood sample. The telomere repeat copy number (T) to single-gene copy number(S) ratio was calculated using the comparative Ct method. Results: The mean and standard deviation of telomere length in the patient and control group was 0.65 ± 0.05 and 0.72 ± 0.07 respectively. There was a statistically significant difference between the two groups. (P = 0.031). Conclusion: Sarcoidosis is an inflammatory disease that can involve many organs. Like other chronic diseases, aging phenomenon occurs in that; which led to decrease cellular and tissue telomere length. This article demonstrates shorter telomere length in Iranian sarcoidosis patients compared to normal population.